ORIENTASI INTERPRETASI MAKNA JIHAD DALAM PANDANGAN HAMKA DI YAYASAN BALQIS, JAKARTA - Hamdani Anwar; Ahmad Zulki; Sudarmono Sudarmono; Zakaria Lubis; Ikhlas Budiman; Fikri Hakim (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Talking about Jihad is a natural thing in modern times, because jihad has always been a constant debate, never ending and has given birth to many scientific works. And jihad is a very unique and interesting theme to research and study.The purpose of this studying to find out more deeply what the meaning of jihad put forward by Hamka in the book of Tafsir Al-Azhar and to find out how jihad is physical and mental according to Hamka in Tafsir Al-Azhar.The method in this research is library research, namely by using the maudhu'i interpretation method (thematic interpretation), which is a discussion of the verses of the Qur'an in accordance with the themes and titles that have been set. The things that are done in this research to identify the verses of the Qur'an that are related to jihad. And only examined one Modern Mufassir, namely Hamka's essay in his book Tafsir Al-Azhar.According to Hamka Jihad is: fighting, sincerity and activities that are driven by the heart with a sincere and sincere feeling, doing amar ma'ruf, nahi munkar, preaching, educating, and nurturing people to religious awareness. As for physical jihad, it is war if ordered by the authorities in a country. While non-physical Jihad is all good deeds that are positive for religion